Linear models least squares and alternatives - Rao, Calyampudi Radhakrishna 1920-2023; Toutenburg, Helge 1943-2009 (Springer series in statistics, 1995)
The material covered will be invaluable not only to graduate students, but also to research workers and consultants in statistics